Geomorphological and paleoenvironmental evolution in the prehistoric framework of the coastland of Mondragone, southern Italy. (10th November 2018) - Aiello, G.; Barra, D.; Collina, C.; Piperno, M.; Guidi, A.; Stanislao, C.; Saracino, M.; Donadio, C.
Abstract: Using morphological, stratigraphic, paleoecological and geoarcheological data, as well as radiocarbon datings, we reconstructed the evolution of the coastal plain of Mondragone, in the northern sector of the Campania Plain, during the last 40 kyr. The Late Pleistocene-Holocene morphodynamics of this coastland were mainly dictated by mutual interaction between tectonics, sea-level fluctuations, Quaternary volcanic eruptions, and subsidence. These processes also influenced the dynamics of prehistoric and proto-historic human populations. Actually, the discovery over the last 25 years of several archaeological sites referable to Upper Paleolithic-Early Iron Age as well as the recent finding of artifacts, fauna and, for the third time in Campania, of Neanderthal human remains in the Roccia San Sebastiano cave, demonstrates that the coastal plain of Mondragone had always hosted human settlements. This constant frequentation is confirmed by, both emerged and submerged, ruins of Roman age and Middle Ages, and the high level of urbanization of the modern town. The interpretation of four borehole stratigraphic sequences down to 22 m bgl, of microfossils analysis and sediment facies highlighted the succession of transition, from marine to freshwater, and continental paleoenvironments in this coastal plain. These wetlands developed in climatic conditions that varied from glacial (Würm) to postglacial phases. Some deposits are interpreted as marshy sediments accumulated in shallow, elongated ponds behind sandy beach or dunes, which existed almost up to the present. The reconstruction of landscape morphodynamic evolution shows that after the "super eruption" of the Campanian Ignimbrite (∼39 kyr BP) the physiography abruptly changed. A wide gulf characterized by gray tuff cliffs and facing northwest formed, along the littoral between the Garigliano and the Volturno river mouths during the volcanic stasis of the Phlegrean Fields, which lasted about ten thousand years after the violent ignimbrite eruption. In this period, the presence of Neanderthal and of a settlement in the Roccia San Sebastiano cave, at the foot of Mt. Massico, is proven by the findings of an excavation. Later (∼20 kyr BP - Holocene), subsidence and sea-level rise activated strong erosion processes due to the postglacial marine ingression, with a consequent rapid shoreline recession and the genesis of transition environments. Finally, according to the results of previous multidisciplinary research carried out on other Campania coastal plains, adjacent or not to the studied area, distinct generations of post-Campanian Ignimbrite - Holocene coastal lakes (lagoons, ponds) and waterlogged environments (marshes, quagmires) were recognized, slightly below and at the current sea-level.